Radionuclide Molecular Imaging of EpCAM Expression in Triple-Negative Breast Cancer Using the Scaffold Protein DARPin Ec1; Molecules; Vol. 25, iss. 20 - Vorobjeva (Vorobyeva) A. G. Anzhelika Grigorjevna; Bezverkhniaia E. A. Ekaterina Aleksandrovna; Konovalova E. V. Elena Valerjevna; Shulga (Schulga) A. A. Aleksey Anatolievich; Garousi Ja. Javad; Vorontsova O. Olga; Abouzayed A. Ayman; Orlova A. M. Anna Markovna; Deev S. M. Sergey Mikhaylovich; Tolmachev V. M. Vladimir Maksimilianovich (2020, 2020)
Title screen